(untitled) (Journal of Multidisciplinary Sciences and Innovations, 2025)
This article explores modern technological approaches for utilizing waste heat energy generated during the operation of industrial boiler plants. By recovering significant amounts of thermal energy typically lost in thermodynamic processes, it is possible to improve energy efficiency and reuse waste heat as a secondary energy source. Various heat recovery technologies are analyzed, including heat exchangers, regenerative boilers, waste heat recovery power generation (WHRPG) based on the Rankine cycle, and absorption chillers. Scientific studies indicate that reusing waste heat can reduce fuel consumption in industrial boiler plants by 10–30% and significantly cut emissions of harmful gases into the environment.